2014
DOI: 10.4049/jimmunol.1303431
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Microparticles Interact with and Support the Proliferation of T Cells

Abstract: Endothelial cells (EC) closely interact with circulating lymphocytes. Aggression or activation of the endothelium leads to an increased shedding of EC microparticles (MP). Endothelial MP (EMP) are found in high plasma levels in numerous immunoinflammatory diseases, e.g. atherosclerosis, sepsis, multiple sclerosis and cerebral malaria, supporting their role as effectors and markers of vascular dysfunction. Given our recently described role for human brain microvascular endothelial cells (HBEC) in modulating imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 52 publications
0
55
0
Order By: Relevance
“…MP were prepared as previously reported67. Briefly, whole blood was centrifuged at 1,500 g for 15 min at room temperature to obtain platelet poor plasma (PPP).…”
Section: Methodsmentioning
confidence: 99%
“…MP were prepared as previously reported67. Briefly, whole blood was centrifuged at 1,500 g for 15 min at room temperature to obtain platelet poor plasma (PPP).…”
Section: Methodsmentioning
confidence: 99%
“…EVs derived from plasmodium-infected red blood cell (MiREVs) are immunogenic and can influence systemic inflammation [16]. They are also known to promote antigen presentation and T cell stimulation [6,16,17]. We have reported that MiREVs contain small regulatory human and plasmodial RNAs, which are readily transferred to various cell types, including human bone marrow-derived endothelial cells, implying their role in host-pathogen interactions [18].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo analysis has shown elevated endothelial EV-leukocyte complexes in plasma from MS patients during disease exacerbation [42]. And binding of endothelial EVs, obtained from blood of patients with severe systemic inflammatory response syndrome, to neutrophils has been demonstrated in vitro [43], as has binding of EVs from BMEC cultures to both monocytes [44] and lymphocytes [45]. That inflammation in and outside the CNS [4651], and adhesion of leukocytes [52], each triggers release of EVs from endothelial cells supports a juxtacrine mechanism for endothelial EVs to transfer junctional proteins to leukocytes at or near the BBB during neuroinflammatory disease.…”
Section: Introductionmentioning
confidence: 99%